Electrochemical characteristics of titanium based biomaterials in artificial saliva - Mareci, D.; Ungureanu, G.; Aelenei, D. M.; Mirza-Rosca, Julia Claudia (Wiley, 2007)
In the last decade, new titanium alloys have been developed in different areas of dentistry, such as Ti6Al7Nb, Ti6Al2Nb1Ta1Nb, and Ti5Al2.5Fe. The aim of this study was to compare the Ti6Al7Nb, Ti6Al2Nb1Ta1Nb, Ti5Al2.5Fe, and Ti6Al4V alloys with the commercial titanium, regarding the corrosion resistance in artiﬁcial saliva. In the electrochemical estimations the polarization data are converted into instantaneous corrosion rate values (Icorr). The passivation properties were comparable for the four alloys. The EIS spectra are best ﬁtted using an equivalent circuit (EC), which corresponds to the model of a two-layer structure for the passive ﬁlm. High impedance values (in the order of 106 V cm2) were obtained from medium to low frequencies for all materials suggesting high corrosion resistance in artiﬁcial saliva. The electrochemical and corrosion behavior of Ti6Al4V is not affected on substituting vanadium with niobium, iron, molybdenum, and tantalum.